A 2020 vision for food, agriculture, and the environment: speeches made at an international conference, June 13-15, 1995 - International Food Policy Research Institute (International Food Policy Research Institute, 1995)
During the past few years, the International Food Policy Research Institute has become increasingly concerned at the apparent complacency in the international community about the future of the world's food situation. As a result, in late 1993 IFPRI began an initiative to look toward the year 2020 to identify the critical issues that must be confronted if the world's growing population is to be fed and the livelihoods of today's poor and hungry are to be improved. This initiative, "A 2020 Vision for Food, Agriculture, and the Environment," has as its goals to seek consensus about the problems of ensuring adequate future food supplies while protecting the world's natural resources for future generations, to create a vision of what the future should look like, and to recommend steps that must be taken immediately to make that vision come true.